Energetic costs of bill heat exchange demonstrate contributions to thermoregulation at high temperatures in toco toucans (Ramphastos toco) - Chaves, Jussara N. [UNESP]; Tattersall, Glenn J.; Andrade, Denis V. [UNESP] (The Company of Biologists, 2023)
Body temperature regulation under changes in ambient temperature involves adjustments in heat production and heat exchange rates between the animal and the environment. One mechanism involves the modulation of the surface temperature of specific areas of the body through vasomotor adjustment. In homeotherms, this thermoregulatory adjustment is essential for the maintenance of body temperature over a moderate temperature range, known as the thermal neutral zone (TNZ). The bill of the toco toucan (Ramphastos toco) has been described as a highly efficient thermal window and hypothesized to assist in the thermal homeostasis of this bird. Herein, we directly evaluated the contribution of heat exchange through the bill of the toco toucan and role of the bill in the delimitation of the TNZ. To do this, we measured metabolic rate (MR), via oxygen consumption, over a range of ambient temperatures from 0 to 35°C. MR measurements were made in birds with the bill intact and with the bill insulated. The limits of the TNZ did not differ between treatments, ranging from 10.8 to 25.0°C. The MR differed among treatments only at elevated temperatures (30 and 35°C), reaching 0.92±0.11 ml O2 g−1 h−1 (mean±s.d.) for the intact group and 1.13±0.13 ml O2 g−1 h−1 for the insulated group. These results indicate that although heat dissipation through the bill does not contribute significantly to widening of the TNZ, it may well be critically important in assisting body temperature regulation at higher temperatures extending above the upper limit of the TNZ.
Keywords: Heat exchange; Metabolic rate; Thermal homeostasis; Thermal neutral zone; Thermal window